2012
DOI: 10.1161/hypertensionaha.111.189589
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Nebivolol and Metoprolol on Insulin Sensitivity and Plasminogen Activator Inhibitor in the Metabolic Syndrome

Abstract: Early generation β-blockers lower blood pressure and reduce cardiovascular morality in coronary artery disease and congestive heart failure, but worsen glucose homeostasis and fibrinolytic balance. Nebivolol is a third-generation β-blocker which increases the bioavailability of nitric oxide. We compared the effect of nebivolol (5mg/d) and the β1-selective antagonist metoprolol (100mg/d) on glucose homeostasis and markers of fibrinolysis in 46 subjects with metabolic syndrome. Subjects underwent a frequently sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 43 publications
3
47
0
7
Order By: Relevance
“…Nebivolol, another β 1 -blocker that has been reported to increase nitric oxide (NO) production from endothelium, thus resulting in peripheral vasodilatation [ 80 ], was not previously shown to significantly affect IS in patients with hypertension [ 79 ] and/ or type 2 DM [ 81 , 82 ]. These beneficial metabolic effects of nebivolol were confirmed in recent studies that showed improvement in glucose metabolism with nebivolol relative to metoprolol in patients with metabolic syndrome [ 83 ].…”
Section: Effects Of Antihypertensive Agents On Insulin Sensitivitymentioning
confidence: 56%
“…Nebivolol, another β 1 -blocker that has been reported to increase nitric oxide (NO) production from endothelium, thus resulting in peripheral vasodilatation [ 80 ], was not previously shown to significantly affect IS in patients with hypertension [ 79 ] and/ or type 2 DM [ 81 , 82 ]. These beneficial metabolic effects of nebivolol were confirmed in recent studies that showed improvement in glucose metabolism with nebivolol relative to metoprolol in patients with metabolic syndrome [ 83 ].…”
Section: Effects Of Antihypertensive Agents On Insulin Sensitivitymentioning
confidence: 56%
“…Of major importance, nebivolol unlike traditional beta blockers does not exert detrimental effects on glycose homeostasis (deterioration of insulin sensitivity and increased risk for new-onset diabetes mellitus) [17] even in combination with diuretics [18], is effective in patients with endothelial dysfunction [19], has a superior effect on central aortic pressure and left ventricular wall thickness compared to other beta blockers [20][21][22] Table 1: Differences between traditional beta blockers and nebivolol in cardiovascular and other disease conditions.…”
Section: Discussion Nebivololmentioning
confidence: 99%
“…Végül pedig a metoprololkezelés növelte az F2-izoprosztán-szintet, míg a nebivololkezelés nem. Tehát a metoprolol ösz-szességében rontotta a glükózháztartást és a fibrinolitikus paramétereket metabolikus szindrómás betegek esetén, míg a nebivololkezelés mentes volt ezektől a kedvezőtlen anyagcserehatásoktól [9].…”
Section: Anyagcsere-semleges ß-Blokkolókunclassified
“…A harmadik generációs β-blokkolókkal és ACEI-, ARB-és CCB-terápiával végzett összehasonlító vizsgálatok adhatnák meg erre a kérdésre az igazi választ. A gyógyszer-kombinációs kezelések során végzett vizsgálatok eddig azt igazolták, hogy a nebivolol, kombinálva az ACEI-és ARB-szerekkel, nem befolyásolták negatív irányba a szénhidrát-és lipidanyagcserét, a hydrochlorothyazid-kombinációkkal összehasonlítva [9].…”
Section: A Vasodilatator β-Blokkolóunclassified